Use of Antidepressant Drugs for Medium or Long Term May Cause Obesity, Diabetes or Renal dysfunction in Women of Reproductive Age Group (Medical Forum Monthly, 2024)
Objective: To assess the use of Anti-depressant drugs are supposed to cause obesity, diabetes or renal dysfunction.Study Design: Cross sectional study.Place and Duration of the Study: The study was conducted in two tertiary care hospitals of Peshawar City of Khyber Pakhtunkhawa in Pakistan i.e. Khyber Teaching Hospital (A public sector health care facility) and Shafique psychiatric clinic (A Private health care facility) Peshawar from February 19, 2016 to May 15; 2016.Materials and Methods: This cross sectional analytical study was carried out in Khyber Pakhtunkhawa in Pakistan to study the side effects of medium term use (03- 36 months) of anti-depressant drugs on the metabolism of glucose and renal functions in women of reproductive age. The study population consists of 165 female (18-45 years). Five ml of fresh fasting venous blood was collected from each subject and was analyzed for HbA1c and renal markers using standard methods & kits.Results: The average serum urea level for both the patients group (SSRI: 22.65 ± 6.41mg/dl and TCA: 18.33 ± 4.53mg/dl) was lower than the control group (24.50 ±5. 14 mg/dl).Similarly the creatinine level of the control group (1.10±0.23 mg/dl) was also higher than both the patients group (for SSRI group was 0.62 ± 0.19 and for TCA was 0.53 ±0.20 mg/dl).The average value of HbA1c was 5.94 ± 0.39, 4.84 ± 0.89, 4.91 ± 0.70 (%) for control, SSRI and TCA groups respectively. Positive correlation was observed between serum urea and drug dosage in mg/day in TCA group (p= 0.01). No significant correlation was found for serum creatinine HbA1c and average glucose level in the patients group (SSRI, TCA) for other variables of interest.Conclusion: Anti-depressant drugs may induce obesity in women of reproductive age if used for medium term, while it may not cause diabetes or renal damage. The effect on the HbA1c level is still not fully understood where as some studies reports its elevation in long term use.